Cibogohilir vellagers products and marketplace - Ratna Komala, Adeh; Aris Astuti, Wati; Razak Abdul Hadi, Abdul (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study aims to see the need for a marketplace for Cibogohilir villagers to market their quality products. The potential of village residents is facilitated with an e-marketplace. The E-marketplace is a digital media that buyers and sellers can use to fulfill their needs that are not limited by space and time. The research method used is a survey method using a questionnaire via a Google form. Respondents were 13 business actors in BUMDes Cibogohilir. The data analysis was carried out through descriptive analysis. Data processing using SPSS. The study results show that the marketplace's level of closeness to partner satisfaction is very close. The community needs a marketplace application system that serves as a medium for Cibogohiir villagers to market their products. The marketplace allows villagers to market their classy and quality products to the outside world.